2022
DOI: 10.3390/rs14102354
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the Mesospheric Winds Observed by Two Collocated Meteor Radars at Low Latitudes

Abstract: This study compares the hourly mesospheric horizontal winds observed by two collocated and independent low-latitude meteor radars operating at 37.5 MHz and 53.1 MHz in Kunming, China (25.6°N, 103.8°E). Upon analyzing simultaneously detected meteor echoes, we find a fixed angular deviation between the baselines of the two meteor radar antenna arrays within the east–north–up coordinate system. Then, we correct the deviation in the antenna azimuth direction using a novel method and recalculate the horizontal zona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…In general, the wind field comparisons between the two radars show strong consistency, and are the same as the results of Zeng J et al (2022). This initial observation suggests the feasibility and reliability of the tidal comparisons in the data.…”
Section: Kmmrssupporting
confidence: 71%
“…In general, the wind field comparisons between the two radars show strong consistency, and are the same as the results of Zeng J et al (2022). This initial observation suggests the feasibility and reliability of the tidal comparisons in the data.…”
Section: Kmmrssupporting
confidence: 71%
“…Moreover, the wind shear occurs around 90 km with lively GW activities. In past, the validity of MF radar measurement has been discussed in the reference Li et al (2015) [35]. In that work, the comparison of wind data and HWM07 shows that the error range was within the acceptable scale, although there was some visible difference between them.…”
Section: Datasets and Analysis Methodsmentioning
confidence: 93%
“…Since 2008, systematic measurements of wind velocity at altitudes of 60-100 km have been made using a medium-frequency (MF) radar and a meteor radar on the same observation platform. These radars have been used for investigations of variations in waves (e.g., tides, planetary waves), responses to events, and lower ionosphere [32][33][34][35]. The prominent advantage of MF radar is its temporal resolution of 3 min compared to the 1 h of meteor radar.…”
Section: Introductionmentioning
confidence: 99%
“…For the most part, the residual RMS (root mean square) of the hourly horizontal velocity provided by the Moncheng meteor radar system is less than 10 m/s. A joint measurement campaign was carried out by Reid et al [46] and Zeng et al [47] to assess the performance and uncertainty of the winds observed by the meteor radar based on the observation from Davis Station in the Antarctic and from Kunming Station at low latitudes, respectively. The uncertainty of zonal and meridional wind observed by the meteor radar for the 1 h average is less than 4 m s −1 near 90 km.…”
Section: Methodsmentioning
confidence: 99%